Geostrategi indonesia dalam menghadapi dinamika global: Ketahanan nasional dan implementasi politik luar negeri - Naja, Marsya Safinatun (Maliki Interdisciplinary Journal, 2025)
This research discusses the concept of Indonesia's geostrategy as a national strategic approach based on geographical conditions and national characteristics. Indonesia's geostrategy is designed to strengthen national resilience and realize state goals through comprehensive and sustainable development, without being expansionist. This research examines various aspects of geostrategy, ranging from the role of Indonesia's geographical region, maritime security challenges, to the implementation of diplomacy as the main instrument in maintaining national stability and sovereignty. Using a qualitative-descriptive approach, data was collected through literature study and policy document analysis. The results show that Indonesia's strategic position brings great opportunities in the maritime sector, but also poses various threats that require an integrated response. Maritime diplomacy and regional cooperation become an important part of the strategy to maintain territorial sovereignty and create a stable strategic environment. In addition, this research highlights future challenges such as climate change, digital transformation and the demographic dividend, all of which demand a more adaptive and innovative update of national strategies. The integration of sustainability principles, technological mastery and improving the quality of human resources are important pillars in strengthening Indonesia's geostrategy. The findings are expected to contribute to the formulation of national strategic policies in Indonesia